Detection and Molecular Characterization of a 16SrII‐A* Phytoplasma in Grapefruit (Citrus paradisi) with Huanglongbing‐like Symptoms in China. Issue 6 (3rd December 2013) - Lou, Binghai; Bai, Xianjin; Bai, Yang; Deng, Chongling; RoyChowdhury, Moytri; Chen, Chuanwu; Song, Yaqin
Abstract In the year 2010, in a survey in Guangxi Province, China, to detect and characterize phytoplasmas in a huanglongbing (HLB)‐infected grapefruit (Citrus paradisi) orchard, 87 leaf samples with symptoms of blotchy mottle were collected from symptomatic grapefruit trees, and 320 leaf samples from symptomless trees adjacent to the symptomatic trees. Nested polymerase chain reaction (PCR) using universal phytoplasma primer set P1/P7 followed by primer set fU5/rU3 identified 7 (8.0%) positive samples from symptomatic samples but none from symptomless samples. Of the 87 symptomatic samples, 77 (88.5%) were positive for 'Candidatus Liberibacter asiaticus' and 5 for both phytoplasma and 'Ca. L. asiaticus'. Sequence analysis indicated that seven 881‐bp amplicons, amplified by nested phytoplasma primer sets P1/P7 and fU5/rU3, shared 100.0% sequence identity with each other. Genome walking was then performed based on the 881 bp known sequences, and 5111 bp of upstream and downstream sequences were obtained. The total 5992 bp sequences contained a complete rRNA operon, composed of a 16S rRNA gene, a tRNAIle gene, a 23S rRNA gene and a 5S rRNA gene followed by eight tRNA genes. Phylogenetic analysis and virtual restriction fragment length polymorphism analysis confirmed the phytoplasma was a variant (16SrII‐A*) of phytoplasma subgroup 16SrII‐A. As phytoplasmas were only detected in blotchy‐mottle leaves, the 16SrII‐A* phytoplasma identified was related to HLB‐like symptoms.